Milk and money - Schmedders, Karl; Johnson, Patrick; Snyder, Charlotte ([London] : SAGE, 2016)
The financial success of dairy farms depends critically on the price of their main output, milk. Large volatility in the price of milk poses a considerable business risk to dairy farms. This is particularly true for family-run dairy farms. The question then arises: how can a farm owner hedge the milk price risk? This case examines the viable options open for farmers and milk producers.
Originally Published in: Schmedders, K., Johnson, P., & Snyder, C. (2008). Milk and Money. 5-407-754. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Dairy products industry -- Case studies; Milk -- Prices -- Case studies